1994
DOI: 10.4141/cjas94-033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maceration at mowing on digestibility and ruminal fermentation of timothy hay in steers

Abstract: Chiquette, J., Savoie, P. and Lirette A. 1994

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…Values reported in Table 2 represent averages of three replications and two forces levels. Maceration is known to increase leaf loss in alfalfa with little effect on timothy (Hong et al 1988;Chiquette et al 1994;Petit et al 1994Petit et al , 1997. However, in the controlled environment, no loss of dry matter was detected during drying and the effect of maceration on CP, NDF, and ADF was nonsignificant.…”
Section: Changes In Chemical Compositionmentioning
confidence: 92%
“…Values reported in Table 2 represent averages of three replications and two forces levels. Maceration is known to increase leaf loss in alfalfa with little effect on timothy (Hong et al 1988;Chiquette et al 1994;Petit et al 1994Petit et al , 1997. However, in the controlled environment, no loss of dry matter was detected during drying and the effect of maceration on CP, NDF, and ADF was nonsignificant.…”
Section: Changes In Chemical Compositionmentioning
confidence: 92%
“…In the companion study of Savoie et al (1996) we did not observe a rapid increase in fermentation rate in RB silage, unlike Muck et al (1989) who followed fermentation patterns in PC silage. A major influence on fermentation rate had been expected because of the massive disruption of cellular integrity resulting from maceration (Chiquette et al 1994). As with PC silages, maceration had little influence on protein solubility in RB silage, even though in this case DM concentration was increased.…”
Section: Silage Qualitymentioning
confidence: 99%
“…Maceration also aids the digestion of forage in the rumen by exposing greater surface area for microbial attack (Chiquette et al 1994;Petit et al 1994). While Charmley et al (1997) did not find this increased digestibility with PC silage, we expect the digestibility of RB silage would be improved with maceration, as is the case with hay (Petit et al 1994).…”
mentioning
confidence: 99%
“…Chiquette et al (1994) reported no increase in total digestibility of macerated timothy hay fed to steers. Frost et al (1995) also observed no improvement in the feed value of macerated ryegrass stored as chopped silage and fed to sheep.…”
mentioning
confidence: 99%